2010
DOI: 10.1007/s12529-010-9126-5
|View full text |Cite
|
Sign up to set email alerts
|

Gender Patterns of Socioeconomic Differences in Premature Mortality: Follow-up of the Hungarian Epidemiological Panel

Abstract: Middle-aged Hungarian men seem to be considerably more vulnerable to the chronic stress of material disadvantage than women. This effect modification by gender might partly be explained by a stronger connection between low SES and depressive symptoms in men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
1
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 56 publications
(78 reference statements)
1
10
1
3
Order By: Relevance
“…Current research mainly supports the idea that health inequality is greater among men. This perspective is probably derived from the literature showing the greater magnitude of inequality in mortality and life expectancy for men . While our study's finding of greater inequalities in women for decayed and missing teeth contradicts those of mortality and life expectancy, it is similar to the pattern of inequalities for heart diseases .…”
Section: Discussioncontrasting
confidence: 60%
“…Current research mainly supports the idea that health inequality is greater among men. This perspective is probably derived from the literature showing the greater magnitude of inequality in mortality and life expectancy for men . While our study's finding of greater inequalities in women for decayed and missing teeth contradicts those of mortality and life expectancy, it is similar to the pattern of inequalities for heart diseases .…”
Section: Discussioncontrasting
confidence: 60%
“…Some studies have found evidence for such a differential association pointing at higher excess mortality in men than in women (Kopp et al, 2011;Takeida et al, 1997;Ahto et al, 2007), but others have not confirmed this (Faller et al, 2007;Yaffe et al, 2003). Whether or not there is a differential mortality rate in men and women is important because it may point at different causal pathways between men and women with depression.…”
Section: Introductionmentioning
confidence: 99%
“…The transition in Hungary from socialism to market economy and democracy may have left suicide figures substantially unchanged, but it has had an effect on morbidity and mortality, rates, and much more strongly among males than females; depression was found to be a major risk factor of premature morbidity and mortality in the male population [3]–[6]. A four-year longitudinal observational study carried out between 2002 and 2006 found that 24% of men in the 40–69 year-old population who died during the study period were severely depressed at baseline, and only 6% of them were treated for depression [7].…”
Section: Introductionmentioning
confidence: 99%